Spontaneous bilateral subclavian vein thrombosis in a 40-year-old man: A case report. Issue 15 (April 2018) - Huang, Chun-Yen; Wu, Yen-Hung; Yeh, I-Jeng; Chen, Yun-Yi; Kung, Fung-Ya
Abstract: Rationale: Paget–Schroetter syndrome (PSS) is an uncommon condition that refers to primary (spontaneous) thrombosis of the deep veins that drain the upper extremities because of anatomical anomalies or repetitive strenuous arm activity. Bilateral spontaneous upper extremity deep-vein thrombosis (UEDVT) is an extremely rare phenomenon in adults, which may be misdiagnosed by physicians in acute settings. Patient concerns: A 40-year-old man presented to our emergency department because of progressive left upper arm swelling for 1 day. He denied fever, chest pain, dyspnea, trauma, or any other systemic disease before. The swollen left arm also had no local heat or redness with normal radius pulsation. He was a laborer who lifted heavy objects. Diagnoses: Blood examination included tests for complete blood count, renal function, liver function, blood coagulation profile, cardiac enzyme levels, and D-dimer level. Results showed that the white blood cell count, renal and liver functions, and cardiac enzyme levels were all within their normal ranges, except for the elevated D-dimer level (1.93 mg/L). Chest radiography and electrocardiography were performed with nonspecific findings. Subsequently, computed tomographic angiography was recommended for the suspected deep-vein thrombosis. The report showed venous thrombosis involving the bilateral subclavian and internal jugular veins. Interventions: Heparin and enoxaparin were prescribed for this patient, with loading and maintenance doses. He was then admitted to our cardiovascular ward for further treatment. Outcomes: The patient was discharged 9 days later in a stable condition. Lessons: Emergency physicians should consider the rare condition of UEDVT when a healthy patient presents with acute arm swelling. Patient history taking should be thorough, especially concerning the risk factors of secondary causes and possible frequent vigorous heavy lifting and overhead motion. Without secondary risk factors, primary upper deep-vein thrombosis might be suspected. Further laboratory tests and imaging studies, especially bilateral imaging, should be arranged to exclude secondary causes and to confirm the diagnosis.